Segmental vitiligo distribution follows the underlying arterial blood supply territory: a hypothesis based on anatomo-clinical, pathological and physio-pathological studies - Benzekri, Laila; Cario-André, Muriel; Laamrani, Fatima Zahrae; Gauthier, Yvon (Frontiers in Medicine, 2024)
Background Segmental vitiligo (SV) is a subset of vitiligo typically characterized by its unilateral distribution. The pathogenesis of SV remains unclear, and until now the two main patterns proposed for SV have lacked biological support. This calls for a new approach. Objectives Use data obtained from anatomo-clinical, pathological, and physio-pathological studies to formulate a new hypothesis on segmental vitiligo distribution and its pathogenesis. Methods Using transparent templates of local arterial blood supply, we evaluated anatomical correspondence (AC) in 140 SV lesions according to the number of SV lesions that fit within the corresponding arterial blood-supply areas. SV lesions were graded as 1 (moderate: AC < 50%), 2 (good: AC > 50%), or 3 (excellent: AC of all lesions). To support this anatomical investigation, we searched for complementary assessments according to the activity of SV lesions. Arterial and periarterial network impairment and inflammatory infiltration were histologically studied using nerve growth factor (NGF) and CD4 and CD8 monoclonal antibodies. Increased blood flow of the underlying arteries was also investigated using thermography and ultrasonography. Results We recruited 140 patients with a sex ratio of 0.8 and mean age 26.13 years. Localizations: head and neck 84.28%; trunk 6.42%; upper limb 5%; genital areas 2.14%; lower limb 1.42%. The AC of each SV lesion with the underlying artery blood supply territory was rated as 72% excellent; 16% good; and 12% moderate. Histologically (40 patients), we found some periarterial network impairments. Thermal asymmetry was significantly associated with active SV (p < 0.001). Conclusion We hypothesized that SV distribution corresponds to the underlying artery blood-supply territory.